2021
DOI: 10.1038/s41467-021-22501-9
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated tau inhibits chaperone-mediated autophagy and promotes tau pathology propagation in mice

Abstract: Disrupted homeostasis of the microtubule binding protein tau is a shared feature of a set of neurodegenerative disorders known as tauopathies. Acetylation of soluble tau is an early pathological event in neurodegeneration. In this work, we find that a large fraction of neuronal tau is degraded by chaperone-mediated autophagy (CMA) whereas, upon acetylation, tau is preferentially degraded by macroautophagy and endosomal microautophagy. Rerouting of acetylated tau to these other autophagic pathways originates, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 91 publications
(148 reference statements)
4
93
0
Order By: Relevance
“…However, recent studies revealed that other modifications of tau, such as acetyl-tau were also associated with the development of AD. The increased level of acetyl-tau affected the synapse and autophagy function associated with the memory deficits in AD [ 58 , 59 ]. Thus, the assessments of acetyl-tau expression after PM exposure in the future researches were needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies revealed that other modifications of tau, such as acetyl-tau were also associated with the development of AD. The increased level of acetyl-tau affected the synapse and autophagy function associated with the memory deficits in AD [ 58 , 59 ]. Thus, the assessments of acetyl-tau expression after PM exposure in the future researches were needed.…”
Section: Discussionmentioning
confidence: 99%
“…Tau acetylation at K174, K274, and K281 have been demonstrated to inhibit synaptic transmission and promote memory deficits in vivo 11 , 12 . Tau acetylation can also regulate its degradation with acetylation of K274 and K281 selectively targeting macroautophagy, while increased pseudoacetylation of these sites exacerbate pathogenesis in some disease models 13 . Overall reduction of tau acetylation also improve outcomes in models of traumatic brain injury 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, full-length tau is preferentially digested through proteasomes [ 51 ]. Recently, it was proposed that a large fraction of tau is degraded by CMA, and upon acetylation, tau is preferentially degraded by macroautophagy and endocytic microautophagy [ 52 ].…”
Section: Tau Degradation Pathwaymentioning
confidence: 99%
“…Tang et al also reported that activated mTORC, which leads to autophagy inactivation, promotes tau secretion into the extracellular space in an exosome-independent manner in neuroblastoma cells, suggesting that tau release is mediated by mTORC via an exosome-free route ( Figure 6 ) [ 63 ]. Recently, it was also reported that CMA blockade upregulated cell to cell propagation in a rodent model of tauopathy [ 52 ].…”
Section: Tau Propagation Due To Autophagy Impairmentmentioning
confidence: 99%